Variations of precipitation and runoff in the Bagmati river basin, Bihar, India. Issue 12 (1st November 2022) - Kumar, Keshav; Singh, Vivekanand; Roshni, Thendiyath
Abstract: The trend analysis of precipitation for four rain gauge stations and runoff for Hayaghat station in the Bagmati river basin is carried out in this work by adopting modified Mann–Kendall and Sen's slope methods. Primary and secondary data are used for finding the monthly, seasonal, and annual trends at four stations. Primary data are the observed rainfall from 1981 to 2013 which were collected from IMD Pune, observed runoff data were collected from CWC Patna and secondary data from the National Center for Environmental Prediction (NCEP)/National Center for Atmospheric Research (NCAR) reanalysis rainfall data for the period 1981–2013. The goals of this research are (i) to determine rainfall and runoff trend analysis, as well as the relationship between observed rainfall data and NCEP/NCAR reanalysis secondary data for four stations and (ii) to find the correlation between observed rainfall data and runoff data for all four seasons. The correlation analysis of observed rainfall and NCEP/NCAR reanalysis data shows a very good correlation ranging between 0.6111 and 0.7435. Rainfall is increasing during and after the monsoon at all selected stations, except during the monsoon season in Dhenge. Correlation analysis of rainfall and runoff shows ranges from 0.3724 to 0.4721 for all the four seasons. The correlation of rainfall and runoff is relatively good in monsoon season. HIGHLIGHTS To determine rainfall and runoff trends, as well as the relationship between observed rainfall data and NCEP/NCAR reanalysis secondary data for four stations. To find the correlation between observed rainfall and runoff data for all four seasons.